Measuring progress in tobacco prevention and control: the role of surveillance - Indu B Ahluwalia; René A Arrazola; Corinne Graffunder (Instituto Nacional de Salud Pública, 2017)
Nearly six million people worldwide die from tobacco-attributable causes every year, making tobacco the leading cause of preventable disease and death. If current trends continue, tobacco use is expected to result in one billion deaths by the end of the century, most of these in low- and middle-income countries. Cigarette smoking is the most common form of tobacco use in most countries, and the majority of adult smokers try their first cigarette before the age of 18...